Does ChatGPT Support Student’s English Writing? Perception Study in Islamic Education Management - Harahap, Sartika Dewi; Hidayani, Syarifah; Hasanah, Nurul (Universitas Pahlawan Tuanku Tambusai, 2025)
The growing use of artificial intelligence (AI) tools has reshaped language learning, offering new opportunities for students to enhance their writing skills. This qualitative study explores the experiences of 27 first-semester students from the Islamic Education Management Department at Institut Jam’iyah Mahmudiyah, Tanjung Pura, in learning English writing through ChatGPT. The study aims to understand how students use ChatGPT as a problem-solving tool when facing difficulties in grammar, vocabulary, and sentence construction. Data were collected through questionnaires and written reflections. The findings reveal that students use ChatGPT to find examples, clarify grammatical rules, and practice sentence formation in various contexts. Many students reported feelings of curiosity, engagement, and self-reflection during the process. The study implies that ChatGPT can serve as an effective learning companion, fostering learner autonomy and motivation in developing writing skills among beginner students in Islamic higher education settings.